Degradation of specific glycosaminoglycans improves transfection efficiency and vector production in transient lentiviral vector manufacturing processes - Williams-Fegredo, Thomas; Davies, Lee; Knevelman, Carol; Mitrophanous, Kyriacos; Miskin, James; Rafiq, Qasim A. (Frontiers in Bioengineering and Biotechnology, 2024)
Both cell surface and soluble extracellular glycosaminoglycans have been shown to interfere with the exogenous nucleic acid delivery efficiency of non-viral gene delivery, including lipoplex and polyplex-mediated transfection. Most gene therapy viral vectors used commercially and in clinical trials are currently manufactured using transient transfectionbased bioprocesses. The growing demand for viral vector products, coupled with a global shortage in production capability, requires improved transfection technologies and processes to maximise process efficiency and productivity. Soluble extracellular glycosaminoglycans were found to accumulate in the conditioned cell culture medium of suspension adapted HEK293T cell cultures, compromising transfection performance and lentiviral vector production. The enzymatic degradation of specific, chondroitin sulphate-based, glycosaminoglycans with chondroitinase ABC was found to significantly enhance transfection performance. Additionally, we report significant improvements in functional lentiviral vector titre when cultivating cells at higher cell densities than those utilised in a control lentiviral vector bioprocess; an improvement that was further enhanced when cultures were supplemented with chondroitinase ABC prior to transfection. A 71.2 % increase in functional lentiviral vector titre was calculated when doubling the cell density prior to transfection compared to the existing process and treatment of the high-density cell cultures with 0.1 U/ml chondroitinase ABC resulted in a further 18.6 % increase in titre, presenting a method that can effectively enhance transfection performance.